The relationship between students’ learning motivation and their speaking performance - Suadi; Owusu Mensah (Journal of Research in English Language Teaching and Linguistics, 2025)
Speaking proficiency is a crucial yet often difficult goal for English language learners, particularly in EFL (English as a Foreign Language) contexts where opportunities for authentic communication are limited. While motivation is widely recognized as a key factor in language learning, its specific link to speaking performance has not been sufficiently explored. This study addresses that gap by investigating the relationship between students’ learning motivation and their English-speaking performance, with a focus on identifying which motivational aspects most influence oral language development. The study adopted a quantitative, correlational-comparative design and involved undergraduate EFL students enrolled in intermediate-level speaking courses at a private university in Indonesia. Data were gathered through a standardized motivation questionnaire and a structured speaking test aligned with international language proficiency benchmarks. The analysis was conducted using SmartPLS 4.0 to assess both the validity of the constructs and the strength of the hypothesized relationships. The findings revealed a clear and positive relationship between learning motivation and speaking performance. Students who demonstrated higher levels of motivation consistently achieved stronger results in their speaking tasks and exhibited greater fluency, confidence, and coherence. Additionally, those with strong motivation tended to show more consistent performance and greater emotional resilience during speaking activities. These results highlight the importance of integrating motivational support into language instruction. Educators are encouraged to adopt learner-centered approaches that foster autonomy, goal-setting, and emotionally supportive learning environments. This study contributes to the growing body of research in English Language Teaching by offering empirical evidence that motivation is a powerful predictor of speaking success and by providing practical insights into how teaching strategies can be optimized to enhance learners’ communicative competence.